2011
DOI: 10.1021/pr200845n
|View full text |Cite
|
Sign up to set email alerts
|

Interactome of the Plant-specific ESCRT-III Component AtVPS2.2 in Arabidopsis thaliana

Abstract: The endosomal sorting complexes required for transport (ESCRT) guides transmembrane proteins to domains that bud away from the cytoplasm. The ESCRT machinery consists of four complexes. ESCRT complexes 0–II are important for cargo recognition and concentration via ubiquitin binding. Most of the membrane bending function is mediated by the large multimeric ESCRT-III complex and associated proteins. Here we present the first in vivo proteome analysis of a member of the ESCRT-III complex which is unique to the pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 100 publications
1
28
0
Order By: Relevance
“…5A), indicating that the two fusion proteins interact. Similarly, coexpression of Vps23 and ESCRT-I protein Vps28 resulted in growth on high selection media, which has been reported previously using the yeast two-hybrid assay (36,61,62). As a negative control and consistent with our in vivo data (Fig.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…5A), indicating that the two fusion proteins interact. Similarly, coexpression of Vps23 and ESCRT-I protein Vps28 resulted in growth on high selection media, which has been reported previously using the yeast two-hybrid assay (36,61,62). As a negative control and consistent with our in vivo data (Fig.…”
Section: Resultssupporting
confidence: 91%
“…Presently, our understanding of ESCRT in plants is relatively poor, and thus, working models based on studies of ESCRT in yeasts and mammals are often employed to infer the mechanisms of ESCRT assembly and function in plants. While this approach has generally proven to be valid because of the overall conserved nature of ESCRT function among evolutionarily diverse organisms, particularly during MVB biogenesis (35,61,62), there are also several features of ESCRT in plants that are distinct, including the ability of TOL proteins to compensate for the lack of ESCRT-0 proteins in terms of ubiquitinated cargo recognition and sorting (16,17). Thus, understanding how different tombusviruses appropriate the plant ESCRT machinery, apparently through different forms of molecular mimicry, as discussed below, not only gives important insight into how tombusviruses manipulate membranes to facilitate their replication but may also provide valuable clues to previously unexplored aspects of normal ESCRT assembly and function in plants.…”
Section: Discussionmentioning
confidence: 99%
“…We tested the ALIX-SNF7 interaction in yeast two-hybrid and bimolecular fluorescence complementation (BiFC) assays (Figure 5;Supplemental Figures 7 and 8). For these assays, we used the two Arabidopsis Vps32/Snf7 homologs SNF7.1 (At4g29160) and SNF7.2 (At2g19830) (Richardson et al, 2011;Ibl et al, 2012). ALIX directly interacted with both SNF7.1 and SNF7.2.…”
Section: Alix Associates With Components Of the Escrt-iii Complexmentioning
confidence: 99%
“…In this study, the Vta1/LIP5 orthologue, AtLIP5 was also identified as an AtSKD1 activating protein. There is also a proteomic report mapping the protein-protein interactions within ESCRT-III in Arabidopsis thaliana (Ibl, et al 2012). In this study, a member of the Vps2 family of Arabidopsis, AtVPS2.2 was used as a bait to identify interacting proteins.…”
Section: Plantsmentioning
confidence: 99%